Organização e disseminação da produção científica dos docentes do CCSH/UFSM em um repositório digital - Vieira, Luciana Corrêa (2013)
In recent years, the continued advancement of information technology has been changing the production process and scientific communication, enabling new forms of access to research results. Universities and research institutions now have new ways to generate, disseminate and preserve knowledge, such as digital repositories, which contribute to increase the visibility of the scientific output of the institution. However, the successful implementation of a repository depends on a consistent policy of information that enables broad dissemination of scientific and count with the participation of the academic community, especially the teachers who are responsible for much of the knowledge generated in the academic realm. Thus, this paper aims to propose a policy organization, dissemination and access to scientific output of teachers in CCSH/UFSM based on free access through a digital repository. Therefore, we carried out a descriptive study, which allowed us to characterize the scientific output of teachers in CCSH, investigate their production practices and dissemination of knowledge and ultimately establish actions to build a digital repository. Among the results, it was found that, despite significant technological changes in the forms of scientific communication and understanding of teachers about the importance of using resources more democratic access to the scientific literature, there is a disagreement about the concepts related to the means of publication and communication of knowledge produced, indicating the need for a work presentation and disclosure of a repository, demonstrating its role in the scholarly communication system, as well as the differences and similarities with other systems of dissemination of scientific production. It also became clear that the concern of teachers in adopting a digital repository is focused on issues related to plagiarism, legitimacy of the result of their research, violation of rights granted to publishers of scientific and requirements of funding agencies, such as Capes. The policy of the organization, dissemination and access to the scientific proposal in this study was prepared considering some essential aspects like information policy goals; responsibilities for managing the repository; organization repository; contents and formats; deposit/submission of documents , legal aspects, access and sustainability of the repository.